Carers' experiences of accessing and navigating mental health care for older people in a rural area in Australia. (1st February 2017) - Dawson, Suzanne; Gerace, Adam; Muir-Cochrane, Eimear; O'Kane, Deb; Henderson, Julie; Lawn, Sharon; Fuller, Jeffrey
Abstract : Objectives: Mental health care for older people is primarily delivered in the community and is largely dependent on informal carers. Mental health policy encourages partnerships between carers and service providers to facilitate service access, coordination and positive experience of care. However, carers often lack information and support from services, with the potential for carer burden, and negative impacts on their own health and capacity to fulfil caring tasks. This paper explores rural carers' experiences of accessing care from a range of services for older people with mental health problems. Method : The Pathways Interview Schedule was used to facilitate 9 in-depth care journey interviews with 11 carers of older people with a mental health problem. Interviews explored their journeys to and through mental health, aged care, primary care and social care services. Framework analysis was used to explore carers' experiences and perceptions of care with a focus on access enablers and barriers. Results: Carers had a significant role in navigating services and operationalising care for their relative. Enablers to accessing care included carer knowledge and workers actively involving carers in planning. Barriers included carer mental health literacy, consumer and carer readiness for services, and worker misinterpretation of confidentiality and privacy laws. Conclusion: Carers should be considered key partners in mental health care planning that crosses service sectors. For this to occur, changes are required at the worker level, including increased communication between mental health workers and carers, and the service level, involving training for staff in interpreting confidentiality and privacy policy.